A STUDY ON THE DEVELOPMENT OF INTERCULTURAL EFFECTIVENESS: INTERCULTURAL PERSPECTIVE AND ACADEMIC ACHIEVEMENT OF EFL LEARNERS - Akyıldız, Seçil Tümen (Fırat University, 2019)
Yabancı dil öğretimi hızla küreselleşen dünyanın vazgeçilmez araştırma alanlarının başında gelmektedir. Bu hızlı küreselleşme geleneksel tanımların da hızlıca değişimine neden olmaktadır. Bu nedenle yabancı dil öğretimi tanımı da -öğrencilerde kültürler arası iletişimsel yetinin kazandırılması- şekline dönüşmüştür. Kültürler arası iletişimin kazandırılması noktasında da eldeki fırsatlar değerlendirilmelidir. Bu bakış açısından yola çıkarak mevcut araştırma Türkiye'deki yabancı dil öğrencilerinin farklı bir kültürle etkileşim sonucu kültürler arası etkinliklerini artırmak ve bu etkileşimin yabancı dil öğrenimlerindeki başarıya katkısını incelemeyi amaçlamıştır.  Bu amaç doğrultusunda Türkiye’nin doğu kısmında bulunan bir şehir olan Elazığ’da bulunan Fırat Üniversitesi ile Türk İşbirliği ve Koordinasyon Ajansı (TIKA) arasındaki bir projeden faydalanılmış ve bu yolla Türkiye’ye formasyon eğitimlerini almaya gelen Gana’lı öğretmen adaylarının yabancı dil öğrencilerine kültürler arası etkililik ve akademik başarı açısından etkisi araştırılmıştır.  Karma yöntem deseniyle yürütülen araştırmadan elde edilen nitel ve nicel veriler öğrencilerin kültürler arası etkinlik düzeylerinde ve academic başarılarında bir artış olduğunu kanıtlar niteliktedir.

Foreign language teaching is one of the key concepts in swiftly globalized world. The recent identification of language teaching is leaning to develop intercultural communicative competence. So, international exchange opportunities may be utilized to develop intercultural communicative effectiveness, one of the components of intercultural communicative competence. Within this perspective this article use the analysis of the data from a project between Fırat University and Turkish Collaboration and Coordination Agency (TIKA) as base. The participants were the Turkish EFL (English as a foreign language) learners and the Ghanaian teacher candidates (GTC). The aim was to investigate the participants’ intercultural effectiveness development and their perceptions of the usefulness of their intercultural interactions on academic achievement in this respect. Data collected from an Intercultural Effectiveness Scale (IES), and interviews were analyzed to address the research questions. Findings, taken from the quantitative and qualitative analysis, show that students developed their intercultural effectiveness levels and increased their academic achievement to some extent. Based on the results intercultural collaborations are discussed to provide intercultural scope and language learning facilities for students.
A STUDY ON THE DEVELOPMENT OF INTERCULTURAL EFFECTIVENESS: INTERCULTURAL PERSPECTIVE AND ACADEMIC ACHIEVEMENT OF EFL LEARNERS